An application of the trial‐based functional analysis to assess problem behavior evoked by ritual interruption. (28th May 2022) - Weyman, Jennifer R.; Bloom, Sarah E.; Campos, Claudia; Garcia, Anna R.
Abstract: Children with autism spectrum disorder engage in restricted and repetitive behavior. Some of these children engage in problem behavior when these rituals are interrupted. The purpose of the current study was to evaluate the use of the trial‐based functional analysis to assess problem behavior related to ritual interruption and to treat the problem behavior using functional communication training plus a multiple schedule. We found that the trial‐based functional analysis correctly identified the presence of a rituals function and the treatment was effective in four of four participants, and the treatment generalized to additional rituals for three of three participants.